A review on the effectiveness of urban solid waste management in Subang Jaya Municipal Council (MPSJ) / Mohammad Syahir Aiman Abd Khair and Puziah Ahmad - Abd Khair, Mohammad Syahir Aiman; Ahmad, Puziah (Faculty of Architecture, Planning and Surveying, 2017)
The Malaysian Solid Waste and Public Cleansing Management Act of 2007 (Act 672) was introduced in order to provide a comprehensive, integrated, cost-effective and sustainable system of solid waste management. This Act granted the Federal Government through the Federal Government Corporation known as the Solid Waste Management and Public Cleansing Corporation (SWCorp Malaysia) an executive power over managing urban solid waste and public cleanliness throughout Peninsular Malaysia. Should the Act be implemented at the state and local government level, solid waste and public cleanliness are managed by concessionaires chosen by the SWCorp Malaysia. Even though the Act had been gazetted by the Parliament, the State Government of Selangor had decided against its implementation. As consequence, on October 16, 2011, the state government terminated Alam Flora Sdn. Bhd (AFSB) as their waste management contractor. This means that local authority (LA) would resume their traditional duty as waste manager with state government as monitoring agency. There are positive and negative impacts resulted from this change in management of solid waste for the LA's. The positive impacts can be seen in terms of budget allocation and LA's level of involvement in the context of local scenario's. Regardless of this issue, LA's to rearrange their environmental management programs as the Federal Government power had been restricted. Termination of the Federal Government concessionaire's contractor (AFSB) caused LA's workload to increase drastically. Hiring new contractor for waste management service provider was time consuming and caused a delay in the management as the new contractor needed time be familiar with the system. Based on the analysis and findings from this research, MPSJ had proven that LAs that had vast resources were capable in managing their own solid waste issues. This obviously came from the initiatives and programmes that had been put together by the management, although there were still rooms for improvements in the future.